Profil Kekuatan Usaha Dalam Memanfaatkan Peluang Usaha Industri Kecil di Pasar - . Supriyanto (Universitas Bandar Lampung (UBL), 2015)
In understanding business positions to be seen from internal and external environment of small industries, a research on the Profile of Business Strength in Using Business Opportunities in Small Industries in Market has been conducted. The objective of this research was to find out and explain profiles of business strength, business opportunities and relationships between them. This research used explanatory survey and associative descriptive method. Research objects were 5 (five) bakery business units with target population of 41 persons. Samples or informants were taken using 50% of cluster sampling or 20 informants. Data were analyzed descriptively and associatively.To be seen from internal environment, the profiles of small industries were in sufficiently strong position. The business strength lied on funding, production, and, marketing. Their weaknesses were in employments. To be seen from employment dimension, all factors still showed weaknesses. The weaknesses lied on entrepreneur ship skills/employments, employees’ skills, working conditions, and opportunities to develop for employees. From external environment profile, the business opportunities of small industries was in sufficiently good position. The good business opportunity was marketing. There were many challenges in funding, production, and employment. In funding dimension, business challenge was in providing grant, using credit, and assistance and education. In production dimension, the business challenges were aids for production infrastructures, suppliers’ abilities, and assistances and educations. In employment dimension, business challenges were in educating employments’ skills and roles of the government/third parties.The SWOT dimension analysis showed that the relationship of profile of strength and opportunity in small industries was in S-O position (strength-opportunity), or in other word, sufficient strength and sufficient opportunity. It indicated that position of small industries to be seen from internal environment was sufficiently strong (S) and from external environment was sufficiently having opportunity (O) in the market. With S-O small industry position, the possible business strategy to do was S versus O. It means that the small industries should keep/improve the existing business strengths and opportunities in the market.